Self-Regulated Learning Bagi Mahasiswa: Pentingkah? - Heni Purwa Pamungkas; Albrian fiky prakoso (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2020)
An indicator of learning process run well can be measured through student’ academic achievement. Self-regulated learning is assumed has a connection with student academic achievement. It is known that every students has self regulatory to control their learning activities. The research used quantitative approach and to examine the effect of student’ self-regulated learning skills on academic achievement. This study involved 162 students. The results showed that self-regulated learning skills influence academic achievement. The higher self-regulated learning skill, the higher academic achievement is achieved. This result useful for further research to develop learning process that provide opportunity to enhance students self-regulated learning skills. DOI: https://dx.doi.org/10.17977/um014v13i12020p069